Do discriminatory pay regimes unleash antisocial behavior? - Kerstin Grosch; Holger A. Rau (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
In this paper, we analyze how pay-regime procedures affect antisocial behavior at the workplace. In a real-effort experiment we vary two determinants of pay regimes: discrimination and justification of payments by performance. In our Discrimination treatment half of the workforce is randomly selected and promoted and participate in a tournament (high-income workers) whereas the other half receives no payment (lowincome workers). Afterwards, antisocial behavior is measured by a Joy-of-Destruction game where participants can destroy canteen vouchers. The data show that low-income workers destroy significantly more vouchers than high-income workers. Destruction behavior is driven by workers who receive payments that are not justified by performance. When all payments are justified, that is in our Competition treatment where all workers participate in a tournament, the difference vanishes. By using a treatment with random payments, we show that unjustifiably-paid workers destroy less when they had equal opportunities to receive a high payment, i.e., when they were not discriminated by the pay regime.
Keywords: C91; D03; J33; J70; M52; 330; antisocial behavior; discrimination; experiment; joy of destruction